Conscious coupling: The challenges and opportunities of cascading enzymatic microreactors. Issue 7 (8th May 2017) - Gruber, Pia; Marques, Marco P. C.; O'Sullivan, Brian; Baganz, Frank; Wohlgemuth, Roland; Szita, Nicolas
Abstract: The continuous production of high value or difficult to synthesize products is of increasing interest to the pharmaceutical industry. Cascading reaction systems have already been employed for chemical synthesis with great success, allowing a quick change in reaction conditions and addition of new reactants as well as removal of side products. A cascading system can remove the need for isolating unstable intermediates, increasing the yield of a synthetic pathway. Based on the success for chemical synthesis, the question arises how cascading systems could be beneficial to chemo‐enzymatic or biocatalytic synthesis. Microreactors, with their rapid mass and heat transfer, small reaction volumes and short diffusion pathways, are promising tools for the development of such processes. In this mini‐review, the authors provide an overview of recent examples of cascaded microreactors. Special attention will be paid to how microreactors are combined and the challenges as well as opportunities that arise from such combinations. Selected chemical reaction cascades will be used to illustrate this concept, before the discussion is widened to include chemo‐enzymatic and multi‐enzyme cascades. The authors also present the state of the art of online and at‐line monitoring for enzymatic microreactor cascades. Finally, the authors review work‐up and purification steps and their integration with microreactor cascades, highlighting the potential and the challenges of integrated cascades. Abstract : The continuous production of high value or difficult to synthesize products is of increasing interest to the pharmaceutical industry. Microreactors, with their rapid mass and heat transfer, small reaction volumes and short diffusion pathways, could be highly beneficial to study chemo‐enzymatic or enzyme‐enzyme reaction systems in continuous flow. In this review we address how microreactors can be combined as well as the challenges and opportunities of integrated cascades with microreactors.